On the run in Siberia - Willerslev, Rane, 1971- (University of Minnesota Press, 2012)
If I had let myself be ruled by reason alone, I would surely be lying dead somewhere or another in the Siberian frost. The Siberian taiga: a massive forest region of roughly 4.5 million square miles, stretching from the Ural Mountains to the Bering Sea, breathtakingly beautiful and the coldest inhabited region in the world. Winter temperatures plummet to a bitter 97 degrees below zero, and beneath the permafrost lie the fossilized remains of mammoths, woolly rhinoceroses, and other ice age giants. For the Yukaghir, an Indigenous people of the taiga, hunting sable is both an economic necessity.